2013
DOI: 10.3390/ijms14011197
|View full text |Cite
|
Sign up to set email alerts
|

Coumarins from the Herb Cnidium monnieri and Chemically Modified Derivatives as Antifoulants against Balanus albicostatus and Bugula neritina Larvae

Abstract: In the search for new environmental friendly antifouling (AF) agents, four coumarins were isolated from the herbal plant Cnidium monnieri, known as osthole (1), imperatorin (2), isopimpinellin (3) and auraptenol (4). Furthermore, five coumarin derivatives, namely 8-epoxypentylcoumarin (5), meranzin hydrate (6), 2′-deoxymetranzin hydrate (7), 8-methylbutenalcoumarin (8), and micromarin-F (9) were synthesized from osthole. Compounds 1, 2, 4, 7 showed high inhibitory activities against larval settlement of Balanu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
(34 reference statements)
1
11
0
2
Order By: Relevance
“…As it has been indicated, there are few reports about the antifouling activity of coumarins, and in all cases the tests conducted were only at laboratory scale (Iyapparaj et al, 2012;Kim et al, 2013;Wang et al, 2013). In this sense, it was found that methanolic extract containing coumarins obtained from marine macroalgae, was able to inhibit completely the byssal thread production and attachment of brown mussel Perna indica (Iyapparaj et al, 2012).…”
Section: Attachment Assaymentioning
confidence: 92%
See 2 more Smart Citations
“…As it has been indicated, there are few reports about the antifouling activity of coumarins, and in all cases the tests conducted were only at laboratory scale (Iyapparaj et al, 2012;Kim et al, 2013;Wang et al, 2013). In this sense, it was found that methanolic extract containing coumarins obtained from marine macroalgae, was able to inhibit completely the byssal thread production and attachment of brown mussel Perna indica (Iyapparaj et al, 2012).…”
Section: Attachment Assaymentioning
confidence: 92%
“…neritina and the hard fouler Balanus albicostatus (Wang et al, 2013). Conversely, hard fouling species such as Balanus amphitrite have not been recruited in our field trials.…”
Section: Field Trialsmentioning
confidence: 95%
See 1 more Smart Citation
“…Existen muy pocos reportes [20][21] acerca de la actividad antifouling de las cumarinas y, en todos los casos, los tests fueron llevados a cabo solamente a escala de laboratorio. Se ha reportado que los extractos metanólicos conteniendo cumarinas obtenidas de macroalgas fueron capaces de inhibir completamente la producción de hilos del biso en el mejillón Perna indica [19].…”
Section: Ensayos De Asentamientounclassified
“…y Hydroides elegans) y ascidias (Ciona intestinalis), manteniéndose el poder antiincrustante durante los 90 días de experimentación (p < 0.05) (Figuras 2 y 3). Los resultados de estos experimentos concuerdan con los hallados para cumarinas aisladas del árbol de canela que evitaron el asentamiento de algas [20] y de cumarinas de hierbas que mostraron efecto antiincrustante sobre briozoos y cirripedios [21]. Las propiedades de las cumarinas fueron intensamente estudiadas en relación con su estructura molecular.…”
Section: Ensayos De Campounclassified